CENTROS EDUCACIONAIS DE SANTO ANDRÉ: NOVAS FORMAS DE ORGANIZAÇÃO DA ESCOLA PÚBLICA - Giro, Emilce Rodrigues Gomes (2008)
This study aims to reflect on the non-formal education and its educational role within the framework of a Citizen School: The Educational Centers of Santo André (CESAs), presenting themselves as a counter-hegemonic project of inclusive school. The (CESAs) are spaces for non-formal education, a field of knowledge still under construction. To that end, this analysis aims to find out what happens to the mediation of the educational process in this other form of organization of public school. The architectural space, new strategies for educating, training of teachers and participation of all actors of the school as: parents, children, teachers and the community in general are considered voices in the management of these institutions. We started from theoretical references for scholars of the current critical-reproduction which examine the school in the context of corporate class. We support ourselves in the school's unique perspective, defended by Gramsci (1981), where the alternative learning happens in the interactions generated in the participatory process in all its social significance. In the initial chapters of historical and bibliographical character, we discuss the implementation of public policies of this nature, which makes use of non-formal education; we finalize our job evidencing the public politics of education developed in (CESAs), exploring, mainly, the artistic languages in the development of the citizenship.(AU)